2000
DOI: 10.1007/s100670050005
|View full text |Cite
|
Sign up to set email alerts
|

How is Gout Managed in Primary Care? A Review of Current Practice and Proposed Guidelines

Abstract: Twelve practices with a total list of 74,111 patients were audited; 429 patients were identified with a diagnosis of gout. A wide variation in various clinical and laboratory assessments was detected. Similar variations were also noted regarding dietary advice and medical treatment. Monitoring of patients was infrequent. As a result of this audit, guidelines are proposed to improve the diagnosis and management of gout in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 7 publications
4
42
0
1
Order By: Relevance
“…Although this approach has been abandoned by most rheumatologists during the past decade, it continues to be used by many primary care physicians [7,8]. This highdose colchicine regimen results in nearly 100% incidence of moderate to severe gastrointestinal intolerance manifested primarily by abdominal cramping and diffuse diarrhea [9••].…”
Section: Management Failure In Acute Goutmentioning
confidence: 99%
“…Although this approach has been abandoned by most rheumatologists during the past decade, it continues to be used by many primary care physicians [7,8]. This highdose colchicine regimen results in nearly 100% incidence of moderate to severe gastrointestinal intolerance manifested primarily by abdominal cramping and diffuse diarrhea [9••].…”
Section: Management Failure In Acute Goutmentioning
confidence: 99%
“…The cornerstone of the prevention and treatment of gout is antihyperuricemic therapy, either by uricosuric drugs or by XO inhibitors, such as allopurinol. The area of gout therapy has been reviewed in multiple recent articles (McCarthy et al, 1991;Star and Hochberg, 1993;Terkeltaub, 1993;Davis, 1999;Pal et al, 2000;Pascual, 2000;Rott and Agudelo, 2003;Terkeltaub, 2003;Bieber and Terkeltaub, 2004;Schlesinger 2004;Pea, 2005;Wortmann, 2005), as well as in various textbooks, and is not discussed herein in detail.…”
Section: A Xanthine Oxidase Inhibitors In the Treatment Of Gout And mentioning
confidence: 99%
“…Studies have also shown that a failure to regulate recurrent gouty episodes not only causes a progression of the disease but also impairs the lifestyle of affected patients [800][801][802][803] . Another parameter worth considering with respect to refractory gout is that approximately 20 % of patients prescribed 300 mg of allopurinol/day attain and maintain serum uric acid levels of 6 mg/dl [ 736,801,804 ] . However, if most patients (80 %) treated with 300 mg of allopurinol fail to obtain therapeutic serum uric acid levels suf fi cient to reduce the number of recurrent gouty episodes, other therapeutic initiatives need to be considered.…”
Section: Refractory Goutmentioning
confidence: 99%